In Vitro Activities of Oxazolidinone Antibiotics Alone and in Combination with C-TEMPO against Methicillin-Resistant Staphylococcus aureus Biofilms - Audrey R. N. Ndukwe; Jilong Qin; Sandra Wiedbrauk; Nathan R. B. Boase; Kathryn E. Fairfull-Smith; Makrina Totsika (MDPI AG, 2023)
Infections caused by methicillin-resistant Staphylococcus aureus (MRSA) are a global health concern. The propensity of MRSA to form biofilms is a significant contributor to its pathogenicity. Strategies to treat biofilms often involve small molecules that disperse the biofilm into planktonic cells. Linezolid and, by extension, theoxazolidinones have been developed to treat infections caused by Gram-positive bacteria such as MRSA. However, the clinical development of these antibiotics has mainly assessed the susceptibility of planktonic cells to the drug. Previous studies evaluating the anti-biofilm activity of theoxazolidinones have mainly focused on the biofilm inhibition of Enterococcus faecalis and methicillin-sensitive Staphylococcus aureus, with only a few studies investigating the activity of oxazolidinones for eradicating established biofilms for these species. Very little is known about the ability of oxazolidinones to eradicate MRSA biofilms. In this work, five oxazolidinones were assessed against MRSA biofilms using a minimum biofilm eradication concentration (MBEC) assay. All oxazolidinones had inherent antibiofilm activity. However, only ranbezolid could completely eradicate MRSA biofilms at clinically relevant concentrations. The susceptibility of the MRSA biofilms to ranbezolid was synergistically enhanced by coadministration with the nitroxide biofilm dispersal agent C-TEMPO. We presume that ranbezolid acts as a dual warhead drug, which combines the mechanism of action of the oxazolidinones with a nitric oxide donor or cytotoxic drug.